Confidential print South-East Europe (Records of the Public Record Office., 1973)
This series contains confidential print relating to South-East Europe. It comprises selected correspondence and papers relating to Albania, Bulgaria, Crete, Cyprus, Greece, Montenegro, Romania, Serbia and Yugoslavia, to 1933 and 1942 to 1946; to Italy and the Vatican, 1919 to 1933 and 1942 to 1946; and to Turkey, 1942 to 1946. The volumes for 1947 contain general correspondence only.